Research on the user comprehensive energy consumption decision-making method based on the evolutionary game - Zhu, Xian Feng; Yao, Jun Wei; Xie, Qiong Yao; Dai, Lu; Yang, Chu Yuan; Wang, Hai Liang; He, Qi; Deng, Ling; Shen, Ran; Zhou, Xiao Xia (Frontiers in Energy Research, 2022)
With the increasing diversification of human energy consumption forms in the integrated energy market, analyzing the comprehensive energy consumption behavior of user groups according to their changing energy demand characteristics is an important issue to be urgently addressed. To solve this problem, an analysis method of user’s comprehensive energy consumption behavior based on the evolutionary game is proposed in this article. First, three types of users including residents, large industries, and commercial users are considered for this purpose. Then, a utility model which takes into account the energy consumption characteristics of these users and their comfort factors is constructed based on the subjective and objective combination weighting method. Thereafter, an evolutionary game theory is used to analyze the dynamic selection process for users by selecting energy suppliers and then using the selection results when the evolutionary equilibrium is reached. Finally, the model is solved by using a distributed iterative method. The correctness and validity of the proposed method are verified by the simulation results.